10-year results of the Birmingham Hip Resurfacing: a non-designer case series. Issue 1 (January 2018) - Hunter, Thomas J.A.; Moores, Thomas S.; Morley, David; Manoharan, Gopikanthan; Collier, Simon G.; Shaylor, Phillip J.
Introduction: Recent controversies surrounding metal-on-metal (MoM) hip resurfacing has led to a substantial decline in its use. Despite this, there is good evidence to support the use of specific implants in select patients. Patients and methods: A retrospective analysis of Birmingham Hip Resurfacing (BHR) patients with a minimum of 10 years follow-up was performed. Functional scoring was performed with the Oxford Hip Score (OHS) and failure was defined as revision for any cause. 111 patients underwent 121 BHR procedures. All patients had a minimum follow-up of 10 years. 70 patients (63%) were male. Mean patient age at surgery was 52.5 years (male 53.9 years, female 48.8 years). Results: Overall survival at 10 years was 91% (97% male, 80% female). There was a statistically significant improvement in OHS postoperatively which remains at 10-year follow-up (p = <0.05). There was no significant difference in scores between the male and female groups. Revisions were most often in patients with smaller component sizes but this was not found to be statistically significant. Conclusions: Our results reflect that of the wider literature in that good outcomes can be obtained with this implant in a select group of patients and results are comparable to that of conventional hip arthroplasty in patients of a similar age.